Design of Public Service Information System - Karnia, Dasri; Purbasari, Yuntari (International Journal of Information Systems and Technology, 2025)
The design of the Public Service Information System aims to create an integrated platform that can improve the efficiency, transparency, and quality of public services. This system is designed to make it easier for the public to access various services. The system development method uses the Software Development Life Cycle (SDLC) approach with the Waterfall model. The system equipped with an administration module allows officers to manage data, process requests, and monitor service performance. The technology used includes the PHP programming language with the Laravel framework, MySQL database, and a responsive user interface using Bootstrap. The conclusion of this design is that the Public Service Information System can be an effective solution to overcome the problems of slow and less transparent public services. With the implementation of this system, it is expected to create faster, more accurate, and more reliable services, thereby increasing public satisfaction and supporting the realization of better governance.